A family of Melnick-Needles syndrome: a case report - Chi Hoon Oh; Chang Ho Lee; So Young Kim; So-Young Lee; Hak Hoon Jun; Soonchul Lee (BMC Pediatrics, 2020)
Abstract Background Melnick-Needles syndrome (MNS) is an extremely rare osteochondrodysplasia caused by a mutation of FLNA, the gene encoding filamin A. MNS is inherited in an X-linked dominant manner. In this study, we describe three members of the same family with MNS, who exhibited different phenotypic severity despite having an identical FLNA gene mutation. Case presentation The patient was 16 months old, with a history of delayed physical development, multiple upper respiratory infections and otitis media episodes. She was referred to our orthopedic clinic because of bowed legs and an abnormal plain chest radiograph. Both upper and lower extremities were bowed. Plain X-rays showed thoracolumbar kyphoscoliosis, with anterior and posterior vertebral scalloping, and thin, wavy ribs. Hypoplasia of the pubis and ischium, with bilateral coxa valga, were also noted. Target exome sequencing revealed a heterozygous mutation of FLNA, c.3578 T > C, p.Lys1193Pro, which confirmed the diagnosis of MNS. Her older sister and mother had minimal deformities of the axial and extremity skeleton, but genetic analyses revealed the same FLNA mutation as the patient. The mutation identified in this family has not been previously reported. Conclusion This report illustrates the potential inherited nature of MNS and the phenotypic variability of clinicoradiologic characteristics. In patients with traits suggestive of MNS, a careful medical and family history should be obtained, and genetic testing should be performed for the patient, as well as all family members.